(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2025)
The paper presents a study on the findings of design data for small-scale experimental models for an electric motor intended for use in the car powertrain system. The first stage describes a procedure for determining the requirements and characteristics of an electric traction motor based on the specifications of the car body, a standardized driving cycle, and technical prescriptions related to the construction of public roads. Considering the particularities of the electric motor load in traction applications, the configuration of a test bench under laboratory conditions is presented. Two experimental models with reduced power at a scale of 1:10 are proposed, which allow for a low-cost analysis of the operation of the actual motor at maximum torque and maximum speed, respectively. A reduced-scale version of the test bench allows the same loading system for the tests of the two experimental models. DOI: https://doi.org/10.36801/apme.2024.1.8